The A/G (–5) polymorphism in the promoter region of the metallothionein 2A gene and breast ductal carcinoma - Forma, Ewa; Bryś, Magdalena; Romanowicz-Makowska, Hanna; Krajewska, Wanda Małgorzata (Menopause Review/Przegląd Menopauzalny, 2008)
Aim: Polymorphisms in the promoter region of metallothionein genes resulting in variation of heavy metal detoxification may be associated with cancer risk. In the present work A/G (–5) polymorphism in the promoter region of the metallothionein 2A gene (MT-2A) in ductal carcinoma of the breast was investigated. Material and methods: Genomic DNA isolated from 75 breast cancer patients and 100 volunteers was used to genotype MT-2A A/G (–5). Polymorphism was determined by automated DNA sequencer ABI PRISM 377. GeneScan Analysis Software ver. 3.7 and DNA Sequencing Analysis Software ver. 3.4.1 was used for interpretation of results. Results: The distribution of the genotypes of the A/G (–5) polymorphism in the promoter region of MT-2A in both controls and patients did not differ significantly (p>0.05) from those predicted by the Hardy-Weinberg distribution. There were no significant differences (p>0.05) in genotype distributions or allele frequencies between subgroups assigned to different Bloom-Richardson grading. Conclusions: The results suggest that the A/G (–5) polymorphism in the promoter region of the MT-2A gene may not be linked with neoplastic transformation of breast ductal carcinoma.